Karte der Jahreszeiten-Klimate der Erde - Troll, Carl (ERDKUNDE, 1964)
The water cycle of physical regions, the life of plants, animals and biocoenoses, including the epidemic carriers of diseases, the annual round of agricultural work, migrations of animals and man, even some customs of peoples and religious festivals follow a seasonal rhythm. A natural classification of climates, which amongst other things must also form the basis for an understanding of the ecological and certain aspects of the economic life on earth, should thus in consequence be based on the seasonal course of the climatic elements. This has been done in the new map of the climatic types of the world which is presented herewith. It is based on three climatic elements. 1 The seasonal course of illumination and solar radiation between the equator and the poles which corresponds to astronomic conditions varying with latitude. 2 The seasonal course of temperature which in addition depends markedly on the distribution of water and land and on altitude. 3 The seasonal distribution of precipitation or the duration of humid periods and humid seasons as mainly conditioned by the circulation of the atmosphere. The interaction of these three climatic distribution pat terns in space - climatic interference - results in the seasonal climates, the basis of zonal gradation of hydrological phenomena (regimes of rivers and lakes, water cyc les etc.) of the climatic zonation of soils, of the belts of vegetation and of the types of biocoenoses. The thermic seasonal climates in their dependence on conditions of insolation and oceanicity or continentality are demonstrated in a series of 15 thermo-isopleths diagrams which by their simultaneous indication of seasonal and diurnal changes of temperature make it possible at a glance to distinguish the climates of polar regions, temper ate latitudes and the tropics, also of the respective altitudinal zones, e. g. the thermic diurnal climates of the cold tropics. The seasonal climates of the tropics, which in contrast to the thermic seasons of higher latitudes are mainly dominated by a seasonal alternation of precipitation, were classified according to the number of humid and arid months as hygric seasonal climates (after W. Lauer). In the periodically humid extra-tropical climates the seasonal course of temperature as well as precipitation must be considered simultaneously. In consequence a great many types of thermic-hygric seasonal climates result from the combination of summer humid - winter dry, winter humid - summer dry, spring humid - winter and summer dry and permanently dry climates with the various gradations of the seasonal course of temperature. In chapter E the different types of such climates (cf. legend to the map) are explained and compared with some characteristic phenomena of the vegetation. A comprehensive exposition of the hydrological, pedological, geomorphological and ecological consequences of the various climates would necessitate an extensive treatment of the natural landscape zones of the earth; such treatment, which will also take into account the vertical zonation, is being prepared by the author as a three dimensional landscape regional ecology of the earth.